Ash Ra Tempel, Manuel Göttsching, and Klaus Schulze - Grönholm Pertti (Cambridge University Press, 2025)
This chapter discusses the work of Manuel Göttsching and Klaus Schulze. Both were founding members of Ash Ra Tempel, a psychedelic rock band active in 1970–75. Their self-titled debut album, released in 1971, is recognised as one of the classic recordings of Krautrock. Later, Ash Ra Tempel would have a deep influence on space rock, electronic music, and ambient music. The chapter provides an overview of the evolution of Ash Ra Tempel, its successor Ashra, and traces the solo careers of Göttsching and Schulze, with a focus on Göttsching. His career spans from the era of Krautrock through the heyday of the electronic Berlin School in the mid-1970s and the birth of electronic dance music in the 1980s. Since 1972, Klaus Schulze has also produced an imaginative and unique body of musical work as a solo artist. Besides several collaborations, he created many pioneering electronic solo albums in the 1970s, and his active career has endured five decades until the present day.
The Cambridge Companion to Krautrock